Effect of Nosodes on Lettuce, Parasitized or Not by Meloidogyne enterolobii - Ferreira, Thais Moraes; Mangeiro, Mariana Zandomênico; Almeida, Alexandre Macedo; Almeida, Rafael N.; Souza, Ricardo Moreira (Homeopathy, 2021)
Background Nosodes are homeopathic preparations (HPs) obtained from tissues or substances associated with the targeted disease or from culture of the pathogenic agent. Nosodes are thought to modulate host resistance, easing symptoms or promoting cure. A few studies have been published about control of plant-parasitic nematodes with HPs, but none with nosodes. Conceptually, nosodes prepared from nematode infective stages might interact with the plant's pathogen-recognition system and initiate or modulate plant resistance to nematodes.Objective Our goal was to investigate whether nosodes prepared from second-stage juveniles (J2) of Meloidogyne enterolobii can affect the moderate resistance already existing in the lettuce cultivar ‘Elisa’.Methods Nosodes at the Hahnemannian concentrations (cH) 6, 18, 30 and 42 were applied on lettuce plants through irrigation, with a constant daily dosage. The nosode treatment started at the seedling stage, before nematode inoculation with 3,000 eggs + J2 per plant. A series of absolute and relative controls, and 10 replicates per treatment, were employed. At harvest, variables related to plant growth and nematode reproduction were assessed.Results The nosode at 6, 18, and 30cH reduced (p <0.05) the nematode reproduction factor and root density. The nosode effect was cH-dependent since nematode reproduction was favored by treatment with 42cH. The nosode also affected (p <0.05) lettuce roots, which presented higher or lower fresh weight and volume depending on the cH applied and the condition—parasitized or not.Conclusion Nosodes obtained from Meloidogyne J2 may affect plant parasitism by nematodes, possibly by interfering with plant resistance. The nature—positive or negative—and intensity of the nosode effect depends on the cH applied to the plants. Further studies are necessary to identify which cH values are more effective in reducing nematode reproduction without causing negative side effects on plant growth.
Keywords: agrohomeopathy; nosode; plant-parasitic nematodes; root-knot nematode